ANALYSIS EXPERIENTIAL FUNCTION OF MAN AND WOMAN IN WRITING OPINION - KHAIRUNNISAH Khairunnisah (Universitas Muhammadiyah Tapanuli Selatan, 2017)
The aim of this study was to describe the types of process of experiential function using by men and women in writing opinion www.kompasiana.com. The research was designed with qualitative descriptive method. The source of the data was men and women’s text who wrote their opinion in Bahasa Indonesia, which wrote at www.kompasiana.com. The data were obtained by implementing analysis. The analysis of this research was interactive method by Miles and Hubermen approach. The research finding showed that the dominant type of process in men’s text is relational process, while women’s text is material process. It was also found that there are five types of process experiential function in men’s text, they are relational process, material process, mental process, verbal process, and behavioural process . while women’s text found six types of process they are relational process, material process, mental process, verbal process, behavioural process and existential process. Women use more relational process than men, and it also found women use more material process than men. The total number of the process of experiential function using by men and women in writing opinion at www.kompasiana.comis different but it did not show a significant differences. The reason of the different between men and women is the different brain structure. It means, between men and women have different skill to thinking, sensing and giving opinion. Thus, between men and women are different in using types of process in rubric opinion. Keywords: Social Functional Grammar, Experiential Function, Gender , Men and Women differences